Subverting History through Parody, Pastiche, and Historiographic Metafiction in Farooqi’s The Merman and the Book of Power: A Qissa - Iftikhar, Hammad; Shaheen, Aamer; Qamar, Sadia (Pakistan Languages and Humanities Review, 2025)
In this research paper, the authors discuss the novel The Merman and the Book of Power: A Qissa by Musharraf Ali Farooq that was published in 2019. It examines the way Musharraf Ali Farooqi (his name is further used throughout the paper in abbreviation as MAF) was experimenting with parody and pastiche to contest existing historical narratives. It challenges the manner of creating and representation of history. The novel is framed by the history of the Middle East and criticizes both colonial and nationalist concepts as well as providing a multifaceted perspective on the past. Through the application of a theory of parody by Linda Hutcheon, the paper demonstrates how Qissa incorporates critical distance and intertextual aspects to disrupt the mainstream histories and elevate the marginal voices. Parody is employed as a means of conversation in the story, challenging the basis of traditional historiography, and redefining the past as something contentious and mutable. Meanwhile pastiche serves to make MAF’s Qissa contemplate mixing styles, genres, and traditions depending on the multifaceted and stratified identities in the Middle East. In this study, Qissa is placed within historiographic metafiction, a genre that is a combination of history and fiction that challenges the authority and objectivity of history. The mixture of myth, folklore and fantasy in MAF’s Qissa’s storyline points to the multiplicity of historical facts and challenges the exclusionary nature of the mainstream historiographical discourse. The paper contributes to the existing debates on the subject of memory, identity, and representation in literary studies. It bridges the gaps in the theoretical knowledge by the application of Hutcheon to a text involving the Middle Eastern setting, providing new information on the functions of parody and pastiche in postcolonial and postmodern literature. Essentially, Qissa is a transformative piece of work, not only in its degradation of the historical accounts of history, but its reinvention of the same to amplify the voices and stories which are not part of mainstream to both criticize and enlighten our perception of the past, our identity, and power.